Az államháztartás inflációs finanszírozása: BUDGET FINANCING WITH INFLATION - Varga, József (Közép-Európai Közlemények, 2020)
The economic policy objective that the state plays an important role in economic life has become more prominent in economics after Keynes’s work has been published. The classical and neoclassical schools, in the context of the dichotomy of economic theory, the split theory of value and money, leave little room for state activity in their theoretical system. The historical experience of monetary theory analyzed in this publication contradicts the neoclassical theory. The practice of financing inflation is closely linked to the functioning of public finances, both at a causal and a consequence level. The study has the presumption, that the state of grace in the world economy, which has been characterized by high levels of economic growth, low inflation and low interest rate levels for nearly a decade, may change in the near future. Inflation is expected to play a larger role in the global economy in financing future public finances. The study examines the impact of inflation on the financing of public finances in the context of an upward trend in inflation rates that is expected to accelerate in the near future. First, based on a Keynesian inflation example, I present the Claassen modeling of the inflation tax based on the volume tax mechanism. This is followed by an examination of the major redistribution mechanisms affecting the state, followed by an analysis of the inflation financing of the general government. This section elaborates on the different characteristics of monetary, opportunity cost, and fiscal seigniorage theories. The analysis establisheds two hypotheses. The first assumption is that, because of its negative impact on the economy, inflation financing is at the end of the range of available assets (a weapon of weak governments). According to the second hypothesis, inflation is only an effective tool in the event of a slight increase in prices through an inflation tax. If the government raises the pace of money issuance beyond one point, this will only result in accelerated inflation and not in tax revenue growth (the "high inflation trap").